2021
DOI: 10.19159/tutad.890935
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Two Commercial Propolis Extracts as Plant Defense Activator and Antimicrobial Agent Against Pseudomonas syringae pv. tomato (Pst) strain DC3000

Abstract: Propolis is a natural bee product that protects the beehives from internal and external factors. It is a natural-complex compound with a wide potential use as an antimicrobial, anti-fungal, and anti-inflammatory effect. The role of propolis as a plant protection agent and an alternative to pesticides is an unexplored area. Here, two different commercially available propolis extracts were evaluated for antibacterial effects on Pseudomonas syringae pv. tomato (Pst) strain DC3000. Also, the activities of defense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Guginski-Piva et al [36] demonstrated that propolis application resulted in the induction of phytoalexins in soybean (Glycine max) cotyledons, potentially helping to control the powdery mildew. Recently, propolis extracts were also tested for their capacity as plant defense activators of the defense response genes WRKY70 and CaBP22 in Arabidopsis thaliana; propolis induced the expression of these genes [50].…”
Section: Propolis As Fungicide and Bactericidementioning
confidence: 99%
“…Guginski-Piva et al [36] demonstrated that propolis application resulted in the induction of phytoalexins in soybean (Glycine max) cotyledons, potentially helping to control the powdery mildew. Recently, propolis extracts were also tested for their capacity as plant defense activators of the defense response genes WRKY70 and CaBP22 in Arabidopsis thaliana; propolis induced the expression of these genes [50].…”
Section: Propolis As Fungicide and Bactericidementioning
confidence: 99%